2017
DOI: 10.7748/phc.2017.e1277
|View full text |Cite
|
Sign up to set email alerts
|

Using electroceutical treatment to reduce symptoms and improve healing in chronic wounds

Abstract: Chronic inflammation in a wound is often associated with infection and biofilm, which are linked to raised matrix metalloproteinases (elevated protease activity) and reduced cell production along with growth hormones in the wound bed. This causes persistent challenges to healthcare professionals and increases the costs of wound management; the related symptoms also affect the quality of life (QoL) of patients living with wounds that are hard to heal. Electrical energy known as the 'current of injury' is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…As bacteria multiply and colonize the host environment, they form a biofilm, which can eventually lead to the development of an infection. However, it has been shown that the application of an externally produced electric field can prevent the transmission of autoinducers; [ 41–43 ] specifically, acyl‐homoserine and autoinducing peptides expression for gram‐negative and gram‐positive bacteria. This concept is depicted in Figure 1b for Pseudomonas aeruginosa (PA01), Acinetobacter baumannii (ACIN), and Staphylococcus aureus (STAPH).…”
Section: Introductionmentioning
confidence: 99%
“…As bacteria multiply and colonize the host environment, they form a biofilm, which can eventually lead to the development of an infection. However, it has been shown that the application of an externally produced electric field can prevent the transmission of autoinducers; [ 41–43 ] specifically, acyl‐homoserine and autoinducing peptides expression for gram‐negative and gram‐positive bacteria. This concept is depicted in Figure 1b for Pseudomonas aeruginosa (PA01), Acinetobacter baumannii (ACIN), and Staphylococcus aureus (STAPH).…”
Section: Introductionmentioning
confidence: 99%